2020
DOI: 10.3390/app10217945
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Analysis for Ultra High Bypass Ratio Geared Turbofan Engines

Abstract: This paper investigates the impact of thermal management methods on the design point and synthesis exchange rates of an ultra-high bypass ratio geared turbofan engine. In a typical thermal management system, where heat is managed by means of heat exchangers that transfer engine waste heat into oil, air, or fuel. However, the utilization of air–oil and fuel–oil heat exchangers has an adverse impact on engine performance. This paper investigates the impact on and engine’s specific fuel consumption and summarizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Required fuel, instead, is calculated by estimating the fuel flow from table of gas turbine data with a radial-basis function interpolation and multiplying it by the step time. These data have been previously computed with the in-house gas turbine performance tool TURBOMATCH [73], with a span of all possible combinations of altitude, Mach and required shaft power from the selected mission. The step adopted for altitude, Mach number and power are 300 m, 0.1 and 100 kW, respectively.…”
Section: Propulsion System Modelingmentioning
confidence: 99%
“…Required fuel, instead, is calculated by estimating the fuel flow from table of gas turbine data with a radial-basis function interpolation and multiplying it by the step time. These data have been previously computed with the in-house gas turbine performance tool TURBOMATCH [73], with a span of all possible combinations of altitude, Mach and required shaft power from the selected mission. The step adopted for altitude, Mach number and power are 300 m, 0.1 and 100 kW, respectively.…”
Section: Propulsion System Modelingmentioning
confidence: 99%
“…In another study using the UHBR GTF engine models [18], several parameters were investigated to determine how TMS solutions may affect the engine performance. In this study, it was shown that there is a strong linear relationship between bypass duct pressure losses and increases in SFC.…”
Section: Uk Aerospace Technology Institute/innovate Uk and Meggitt Pl...mentioning
confidence: 99%
“…• The waste heat produced in UHBR GTFs is projected to be significant (up to 275 kW per engine for an Airbus A320-sized UHBR GTF aircraft [18]). This heat is not expelled along with the exhaust gases and require dedicated cooling.…”
Section: Heat Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation